(untitled) (Revista Direito em Debate, 2020)
The article is based on dialogue with a National Insitute of Social Security (INSS) server about the security benefits required by Kaingang indigenous people. The Kaingang, according to IBGE (2012), correspond to approximately 38,000 people and the Community studied, called “Terra Indígena Foxá”, is located in the urban context of Lajeado/RS city. The aim of this study was to identify the challenges of access to Social Security rights by members of the Kaingang Foxá indigenous community. From the methodological point of view, this was a qualitative research and the methodological procedures consisted in a biographic, documental and field research on access to Social Security rights by indigenous peoples, based on reports from a National Institute of Social Security (INSS) server. Finally, it was found that there are no social security benefits for the Kaingang indigenous people investigated due to their indigenous status, and this population need to fill the same requirements as non-indigenous to receive any Social Security benefits. However, due to the activities performed by the indigenous people, these are framed as special insured, and this quality is proven through the certificate issued by FUNAI, which describes the condition of indigenous people and the activities developed.